'The facts cannot be denied': legitimacy, war and the use of chemical weapons in Syria. Issue 2 (3rd July 2017) - Geis, Anna; Schlag, Gabi
ABSTRACT: The enduring war in Syria is the most recent case that has triggered fierce debates within the international community, including at the UN Security Council, about how to respond to massive human rights violations in conflicts. In August 2013, one outrageous incident – the use of chemical weapons in the Ghouta area – (initially) seemed to push some liberal democracies towards military intervention in Syria. Although the videos showing the death of civilians spread worldwide via YouTube, the political impact of these images was mixed. Reflecting on the relation between the circulation and display of video images of suffering and their impact on US politics, we address two related questions in this article: first, how did the US administration react to the terrifying videos of people dying in Syria, people who had presumably been attacked by chemical weapons? Second, how was this incident framed in political discourse in the United States? The aim of this article is to understand the ambivalent and contingent effects of media images on decision-making processes regarding the use of force by liberal democracies in response to massive violations of human rights and international law. We argue that the publication of the videos in question initiated a policy change on the part of the US administration, although it did not result in a military response to massive human rights violations.